A LITERATURE REVIEW ON THE EFFECTIVENESS OF SELF-REGULATED LEARNING IN E- LEARNING IN TERTIARY EDUCATION - Huang Xiao, Fairuz A’dilah Binti Rusdi, Julia Tan Yin Yin (Chelonian Research Foundation, 2023)
E-learning has become a common mode of learning among students of tertiary education, and self-regulated learning skills has hence become a crucial skill. This review concludes the analyses and discussions regarding the definitions and characteristics of self-regulated learning, the tools of measurement, and results of efficacy of the relevant literature, as well as investigate the personal and external factors that increase the effectiveness of self-regulated learning. Research has found that the personal factors that lead to effective self-regulated learning online mainly include goal-setting, time management, interaction with friends, and the conditions of the environment where they perform online learning. On the other hand, the external factors include the environment of the e-learning platform and the support of the tutors, specifically in the aspects of the analyses of data, design of the course structures and lessons, learning materials and virtual rewarding systems. In this study, apart from focusing on the effectiveness of self-regulated learning in e-learning, another major aim is to gather the practical measures that can be taken by the tutors and students to increase the learning efficacy of the students. Although there is controversy in some of the effective measures taken by tutors and students, they have provided additional information to the study regarding the effectiveness of self-regulated learning in e- learning, and hence will be able to provide future researchers with different perspectives to perform studies from. Keywords: E-learning; Online self-regulated learning; tertiary education; learning outcomes